Empowering Girls: Kashmiri Contributions to Education in Jammu and Kashmir - Shujaat Yousuf pirzada (RADJA PUBLIKA, 2025)
This research paper explores the significant contributions made by Kashmiri individuals, government initiatives, and non-governmental organizations in promoting and empowering girls’ education in Jammu and Kashmir. From pioneering figures like Begum Zaffar Ali to impactful schemes such as UMEED, KGBV, and Tejaswini, the study highlights a transformative journey toward gender-inclusive education. It investigates the socio-economic and cultural challenges that hinder female literacy and examines ongoing efforts to overcome these barriers. Through data analysis, program evaluations, and historical insights, the paper aims to present a comprehensive overview of the progress made and the road ahead for ensuring equitable educational opportunities for girls in the region.